Do NEETs Need Grit? - Silvia Mendolia; Ian Walker (Institute for the Study of Labor (IZA), 2014)
This paper investigates the relationship between personality traits in adolescence and education and labour market choices. In particular, we investigate the impact of grit (a tendency and ability to sustain interest in long term goals - perseverance) on the risk of youths being NEET "Not in Education, Employment or Training". Thus, our focus is on early drop-out from the labour market and education at age 18-20. Individuals with high levels of grit are less likely to be out of education or employment, while low self-esteem and external locus of control increase the chances of experiencing these conditions. We use propensity score matching to control for a rich set of adolescent and family characteristics and our results show that personality traits do affect education and employment choices. We test the robustness of our results using the methodology proposed by Altonji et al. (2005) that consists of making hypotheses about the correlation between the unobservables and observables that determine the outcomes and the unobservables that influence personality.
Keywords: I10; I21; 330; personality; NEET; grit; locus of control; self-esteem